Nosocomial infections in neonatal units in Turkey: epidemiology, problems, unit policies and opinions of healthcare workers - (:unkn) unknown (TURKISH J PEDIATRICS, 2010)
Turkish Neonatal Society Nosocomial Infections Study Group. Nosocomial infections in neonatal units in Turkey: epidemiology, problems, unit policies and opinions of healthcare workers. Turk J Pediatr 2010; 52: 50-57. The epidemiology of nosocomial infections in Turkish neonatal intensive care units (NICUs) shows that nosocomial sepsis is an important problem, especially for very low birth weight (VLBW) infants, and gram-negative agents, particularly Klebsiella species, are still the major causes of nosocomial infections. Sepsis frequency was 6.4%, ranging from 2.1 to 17%, in 16 centers in Turkey. Sepsis frequency was 22% in infants <1500 g, 6% in those 1500-2500 g, and 3% in those >2500 g. Sepsis-related mortality was 24.4 for 100 sepsis cases, ranging from 0 to 75 for 100 cases. Ventilator-associated pneumonia frequency was 1.7%, catheter-related infection frequency was 0.14% and urinary tract infection frequency was 3.7%. Healthcare workers (HCWs) complain of the inadequacy of some basic facilities and of staffing; however, they are aware of the causes and solutions and are willing to overcome this major health problem. We conclude that Turkish neonatal HCWs are quite optimistic about preventing neonatal nosocomial infections.
Keywords: nosocomial infection; newborn; epidemiology; infection control; OUTCOMES; SEPSIS; SURVEILLANCE; DEFINITIONS; INFANTS